Potential problems of partial resection for colitis-associated cancer in a patient with ulcerative colitis: case report. Issue 3 (22nd March 2021) - Horio, Yuki; Uchino, Motoi; Kihara, Takako; Bando, Toshihiro; Kuwahara, Ryuichi; Minagawa, Tomohiro; Kusunoki, Kurando; Watanabe, Kenji; Hirota, Seiichi; Ikeuchi, Hiroki
Abstract: Total proctocolectomy and an ileal pouch-anal anastomosis are recommended as the standard procedure for ulcerative colitis (UC)-colitis-associated cancer (CAC). However, several studies have reported the partial colectomy and endoscopic resection of UC-CAC in recent years. We present a surgical case of UC-CAC that was detected at a site that had not been diagnosed preoperatively, and we report potential problems of partial colectomy and endoscopic resection through this case. Considerations of synchronous and metachronous cancer/dysplasia are important before partial resection is planned for CAC in UC. Moreover, it should be noted that endoscopic resection at the anal site can be a risk factor for pouch surgery failure due to fibrosis after resection.